MEMBANGUN KEBAHAGIAAN GEOGRAFIK - Sudarma, Momon (Rizki Offset, 2011)
If there are people who feel comfortable, stay in one place, then that is characteristicÂ of people who have geographic happiness. Unfortunately, the natural character andÂ management of everyoneâs life, not always able to deliver himself geographic happiness.Â Existing conditions is the emergence of peopleâs lifestyles are not comfortable, orÂ restless living in the area.Keywords: Geographic happiness, geography education.